2019
DOI: 10.1159/000504380
|View full text |Cite
|
Sign up to set email alerts
|

From Perception to Action: The Role of Auditory Input in Shaping Vocal Communication and Social Behaviors in Birds

Abstract: Acoustic communication signals are typically generated to influence the behavior of conspecific receivers. In songbirds, for instance, such cues are routinely used by males to influence the behavior of females and rival males. There is remarkable diversity in vocalizations across songbird species, and the mechanisms of vocal production have been studied extensively, yet there has been comparatively little emphasis on how the receiver perceives those signals and uses that information to direct subsequent action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Also, neurotoxic lesions of the NCM resulted in a decrease in tutor song preference (measured by selective approach behavior) in adult male zebra finches [14]. Similarly, it was found that CM lesions in adult female zebra finches and Bengalese finches altered the expression of song preference [58,59]. In the future, studying the correlation between behavior and neural activity as well as how behavior changes as these brain areas are manipulated will serve to more accurately interpret previously reported songrelated preference behaviors.…”
Section: Neural Mechanisms Underlying Song Memorymentioning
confidence: 89%
“…Also, neurotoxic lesions of the NCM resulted in a decrease in tutor song preference (measured by selective approach behavior) in adult male zebra finches [14]. Similarly, it was found that CM lesions in adult female zebra finches and Bengalese finches altered the expression of song preference [58,59]. In the future, studying the correlation between behavior and neural activity as well as how behavior changes as these brain areas are manipulated will serve to more accurately interpret previously reported songrelated preference behaviors.…”
Section: Neural Mechanisms Underlying Song Memorymentioning
confidence: 89%
“…BFs and domestic canaries are captive species and swamp sparrows and Lincoln's sparrows are wild, yet our data suggest a similar basis of song evaluation in all four species. Our data reveal a broadly relevant pattern of song evaluation in a species that is especially useful for neurobiological studies in the laboratory [e.g., 41,42], opening the door to additional investigations of how preferences develop, how they are encoded in auditory processing, and how that information is used to direct selective mate choice behaviors. Curiously, not all of the females that we sampled expressed the same preference for accelerated tempo.…”
Section: Considering Possible Benefits Associated With Female Preferementioning
confidence: 99%
“…While the changes occurring in the neural network involved in vocal imitation and production have been studied in detail (for example, reviewed in [ 64 , 65 ]), the role of auditory forebrain areas in providing sensory feedback in VPL has not been studied in detail, but is receiving more and more attention [ 66 ]. In songbirds, neurons in the auditory forebrain were shown to encode information about the category of a vocalization but also about the identity of the emitter [ 67 , 68 ].…”
Section: The Behavioural Decision-making Spacementioning
confidence: 99%
“…Although we are aware that recording neural responses from auditory brain regions cannot be a standard procedure in every animal model used to study VPL, we want to briefly highlight the importance of the comparative study of the neuronal basis of VPL. While the changes occurring in the neural network involved in vocal imitation and production have been studied in detail (for example, reviewed in [64,65]), the role of auditory forebrain areas in providing sensory feedback in VPL has not been studied in detail, but is receiving more and more attention [66]. In songbirds, neurons in the auditory forebrain were shown to encode information about the category of a vocalization but also about the identity of the emitter [67,68].…”
Section: (B) Neuronal Validation Of Vocal Production Learning Via the Receivermentioning
confidence: 99%